STRAIN DIFFERENCES IN TWO SPECIES OF CALLOSOBRUCHUS (COLEOPTERA: BRUCHIDAE) DEVELOPING ON SEEDS OF COWPEA {VIGNA UNGUICULATA (L.)} AND GREEN GRAM {V. RADIATA (L.)} - ROESLI, RENNIE (BIOTROPIA, 2011)
Ovipositional behaviour, development period, and density effect on adult survival of C. maculatus strains from Indonesia, Nigeria, and Yemen, and C. chinensis strains from Indonesia and Kenya on cowpea and green gram were studied at 20°C and 70% relative humidity. Variations on ovipositional behaviour were found among C. maculatus as well as among C. chinensis strains. Variations on developmental period were found only among C. maculatus strains. The developmental period of Callosobruchus spp. was shorter on green gram than that on cowpea. Density effect was remarkably found only on adult survival of C. maculatus Yemen strain. These results make useful contribution to the species biology, and have important implication if strains of these species are accidentally imported to countries, or when new legume crops are introduced.